God of Battles: Holy Wars of Christianity and Islam by Peter Partner. Princeton, New Jersey: Princeton University Press, 1998, 364 pp. (American Journal of Islam and Society, 2000)
This is a study of warfare fought in the name of God by Jews, Christians, andMuslims from biblical until modem times. The book is impressive in its scopeand in the wide range of authorities consulted; the author has gone out of hisway to be neutral and impartial. In his introduction, for example, Partner recognizesthat "less than half a century ago, unconscious of their own arroganceand inaccuracy. Westerners used to write confidently about something theycalled the Arab mind" (p. xix). The book's critical apparatus is nearly perfect:there is a glossary, a chronological table, and an index; and, in addition to ashort bibliography with the notes to each chapter, there is a brief reading list ondifferent topics. This means that students will find the book easy to use.Having said this, readers should be warned that, like most academicresearch, the general tone is dogmatically secular and cynical about spiritualmotives. Although the author criticizes the prejudices of earlier historians, hehimself speaks of Islam as "a program of conquest" and states that "Muslimsset themselves almost from the outset the task of Islamizing the whole worldby force of arms" (p. 38). Despite his remarks on the greater jihad, referring tothe inner spiritual struggle against evil, there is little recognition of Islam as aspiritual message; he says that Muhammad ''came to warn, perhaps also to conquer"(p. 42). Indeed, the striving denoted by the verb jahada is primarily spiritualor moral as in the admonition to the Prophet: "Strive hard against thedeniers of the truth and the hypocrites" (9:73). Other passages indicate that theQur'an itself is the instrument with which believers must strive against unbelievers(25:52; 66:9). As Seyyed Hossein Nasr says, concerning the concept ofjihad, "Its translation into 'holy war,' combined with the erroneous notion ofIslam prevalent in the West as the 'religion of the sword,' has helped to eclipseits inner and spiritual significance."1 All external forms of struggle, such asfighting ignorance and injustice, are incomplete without the inner struggle, andthe result of that struggle will be peace and love: "Repel evil with that whichis better. Then he between whom and thee there was enmity will become asthough he had always been a bosom friend" (41:34) ...